Pengaruh Produk Domestik Regional Bruto, Tingkat Pendidikan dan Kesehatan Terhadap Penyerapan Tenaga Kerja di Indonesia Tahun 2017-2023 - Silvie Putri Wahyu Efendi; Ruth Eviana Hutabarat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the impact of GRDP, education level, and health on employment in Indonesia during the period 2017-2023. A quantitative approach is used in this study by applying panel data regression analysis using secondary data available from BPS. The research findings identify that GRDP has a positive and significant impact on labor absorption in Indonesia. Education level also has a significant positive impact, while the health variable identifies an insignificant negative impact on employment. Together, these three variables have a positive and significant impact on labor absorption in Indonesia. Overall, GRDP, education level, and health are able to explain 99.8% of the variation in labor absorption in Indonesia during the period 2017-2023.